Modelo teórico de categorização dos riscos provenientes da implantação da Indústria 4.0 no setor manufatureiro - Soltovski, Ramon (2020)
Although the theme of industry 4.0 is being discussed a lot, many uncertainties are still present and issues related to the risks involved are little debated. In this context, understanding what they are and how to organize the negative risks arising from the concepts and technologies of the Fourth Industrial Revolution for companies and the entire value chain involved, can help in facing the challenges that may arise. Thus, this work aims to build a theoretical model for categorizing such risks within the industrial scope. For this, a systematic bibliographic review (SBR) was developed, according to the Methodi Ordinatio of Pagani, Kovaleski and Resende (2015). The bibliographic portfolio obtained allowed, through a thematic analysis, the mapping of 28 risks that were divided into four dimensions based on based on the Tipple Bottom Line (TBL) sustainability concept: Economic Risks, Social Risks, Environmental Risks and Technological Risks, and later in eleven subdimensions. Then, it was noticed relationships between the dimensions, in which risks can be contained in more than one dimension simultaneously. These relationships were later represented through the construction of a theoretical framework. Finally, this framework enabled the development of the theoretical categorization model that allows the allocation of risks from Industry 4.0 in 15 categories and 4 levels. Each level represents how many dimensions the same risk can have an effect, for example, a level I risk can have an effect on a single dimension, a Level II risk on two, and so on. After building the categories, the 28 risks previously mapped were categorized according to the model. The categorization allowed to understand how the risks behave within the dimensions, their relationships and how future ones yet to be mapped in later works can be grouped. The model proved to be flexible for applications in a practical perspective, in which managers or specialists can categorize risks based on different contexts. This study contributes to the academy by helping to build a greater theoretical contribution on the issue of risks in Industry 4.0, for companies that can better prepare for the possible challenges encountered in the context of the Fourth Industrial Revolution and for the social environment that can benefit from discussions brought about by risks related to human capital issues within corporate boundaries, issues that involve an entire society and also ethical-legal issues.